Case Report of Scrub Typhus (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Scrub typhus is an acute, febrile, infectious illness that is caused by Orientia tsutsugamushi. Scrub and murine endemic typhus infections are under-diagnosed causes of febrile illness across the tropics, and it is not known how common they are in Bangladesh. Here reporting a case who presented with high grade fever for 7 days associated with headache, abdominal discomfort, cough and receiving inj ceftriaxone for 2 days considering as a case of enteric fever. Forty-eight hours after admission, the presence of continued high grade fever, conjunctival congestion, headache, loose motion, cough, low platelet, elevated transaminase raised the possibility of a different aetiology. The two most likely differentials being dengue and malaria. Finally, typhus was discovered due to history of field visit, presence of eschar and raised titre of WF OXK antigen. All other causes of fever were ruled out by history, clinical examination and relevant investigations. Patient was treated with capsule doxycycline and other supportive therapy and become afebrile within 48 hours. This uncommon clinical scenario should be taken into account in the management of patients with high fever on admission.J Bangladesh Coll Phys Surg 2018; 36(3): 123-127